Efficacy of initial methotrexate monotherapy versus combination therapy with a biological agent in early rheumatoid arthritis: a meta-analysis of clinical and radiographic remission. Issue 7 (26th April 2010) - Kuriya, B; Arkema, E V; Bykerk, V P; Keystone, E C
Abstract : Objective: The target outcome in early rheumatoid arthritis (ERA) is now remission. This meta-analysis compared the efficacy of initial methotrexate monotherapy versus combination therapy (methotrexate plus biological agent) for clinical remission and radiographic non-progression among ERA patients with minimal or no previous methotrexate exposure. Methods: A systematic search was performed for randomised controlled trials of ERA using predefined criteria. A random effects model was used to pool the risk ratio (RR) for clinical and radiographic remission at 52–56 weeks of follow-up. Results: Seven trials of combination therapy with infliximab, adalimumab, etanercept or abatacept were included. The majority of studies defined clinical remission as a 28-joint disease activity score (DAS28) of 2.6 or less. Radiographic non-progression was primarily defined as a modified total Sharp score change of less than 0.5 units. All trials demonstrated risk estimates in favour of combination therapy: the pooled RR for achieving clinical remission was 1.74 (95% CI 1.54 to 1.98) and for radiographic non-progression was 1.30 (95% CI 1.01 to 1.68). Significant heterogeneity among studies for the latter outcome was detected (p<0.001). Conclusions: The efficacy of combination therapy with a biological agent is superior to methotrexate monotherapy for remission. Combination therapy has a greater initial effect on clinical remission than radiographic non-progression. Uniform definitions of remission are needed and the proportion of subjects who achieve the combined endpoint of clinical and radiographic remission should be considered as a meaningful outcome in future studies of ERA.